EVALUASI SISTEM PENGENDALIAN INTERN TERHADAP PRODUK RUSAK - Anggreini, Trifena Ayu; Sulistyawati, Ardiani Ika (Solusi, 2023)
Internal control system is a set of policies and procedures to protect the company's assets from all forms of abuse, ensure the availability of accurate accounting information of the company, and ensure all provisions (regulations) of management policies have been adhered to   accordingly by all employees of the company. Inventory security issues are the main problem experienced by every type of retail business. A good internal inventory control system is needed by retail companies because it is able to minimize these risks.The object in this research is CV Top Album. The purpose of this research is to find out and analyze the description of the internal control system for damaged products applied to CV Top Album. The type of research used in this research is qualitative research type, while the method in data collection in this research is interview, obsevation, documentation. From the results of this study shows that there are still some problems in internal control of damaged products causing material losses and production delays due to damaged products.